Kajian soal pada buku teks matematika kelas v kurikulum 2013 revisi 2018 berdasarkan literasi matematika - Muharomah Muharomah; Siti Kamsiyati; Anesa Surya (Didaktika Dwija Indria, 2021)
This study aims to analyze the questions on grade five mathematics textbook 2018 revision of the 2013 curriculum based on mathematical literacy. The sample of this study is a competency test item on each basic competency. This study use descriptive qualitative method. Data collection in this study use document review. Data analysis in this study use the Miles and Huberman’s model which consist of data reduction, data display, and conclusion. The results of this study is questions that include mathematical literacy from total number of competency test is 53 % or 56 questions. The level of mathematical literacy questions is only at level 1 until level 3 with a specification of level 1is 9 % or 5 questions, level 2 is 41 % or 23 questions, and level 3 is 50 % or 28 questions.